THE EFFECT OF APPLICATION OF GOOD CORPORATE GOVERNANCE ON FINANCIAL PERFORMANCE WITH THE CAPITAL STRUCTURE AS VARIABLE MODERATING ON COMPANY MANUFACTURING REGISTERED IN IDX - Lusiana, Lusiana (Asosiasi Dosen Akuntansi Indonesia, 2018)
This study aims to examine and analyze the effect of good corporate governance indicators consisting of institutional ownership, managerial ownership, the audit committee, the independence of the commissioners and the independence of the board of directors is partially affected or simultaneously to the financial performance of the companies listed in the Indonesia Stock Exchange and also to test and analyze whether the ability of capital structure may moderate the relationship between good corporate governance variables with an indicator that consists of institutional ownership, managerial ownership, the audit committee, the independence of the commissioners and the independence of the board of directors at companies listed Indonesia Stock Exchange. The population in this study are all manufacturing companies in the Indonesia Stock Exchange. Of the 143 companies as population samples taken as many as 20 companies were determined by purposive sampling method. The analytical method used is multiple linear regression analysis and residual test. Results of testing the first hypothesis is partially shows that institutional ownership and managerial ownership have a significant effect on financial performance, while simultaneously showing that variable institutional ownership, managerial ownership, the audit committee, the independence of the commissioners and the independence of the board of directors affect the financial performance. The second hypothesis testing showed that the capital structure is not able to moderate the relationship variables institutional ownership, managerial ownership, the audit committee, the independence of the commissioners and the independence of the board of directors of the financial performance of companies listed on the Indonesia Stock Exchange.